Exploring the potential of community health workers in type-2 diabetes and hypertension management in Cambodia - Savina Chham; Por Ir; Josefien Van Olmen; Veerle Buffel; Ngovlily Sok; Vannith Hay; Willem van de Put; Wim Van Damme; Edwin Wouters (PLoS ONE, 2026)
The burden of type-2 diabetes (T2D) and hypertension (HTN) in Cambodia is a major concern. The government and donors have introduced several interventions, yet human resource shortages hamper their implementation. Community health workers (CHWs) can be a valuable additional resource for health in T2D and HTN management. The current study aimed to assess (1) CHWs’ knowledge, attitude, and practices (KAP) in T2D and HTN management and (2) the potential health system barriers for incorporating CHWs in T2D and HTN management. This mixed-method study comprised a survey among 153 active CHWs to assess their KAP towards T2D and HTN, and semi-structured interviews with key informants were conducted to understand the challenges of the health system and propose solutions in incorporating CHWs in T2D and HTN management. Approximately 90% of CHWs correctly answered general knowledge questions on NCDs, risk factors, and prevention; however, only around 20–40% correctly answered questions on family history or tobacco use as risk factors. Most respondents appeared to have positive attitudes and have been practicing some activities related to T2D and HTN. Both financial and non-financial resource constraints were cited as challenges of the health system; therefore, re-structuring the definition of CHWs’ roles and responsibilities, and assessing the need and workload have been proposed as ways forward to effectively incorporate CHWs in T2D and HTN care. CHWs in Cambodia have shown their potential in T2D and HTN management; however, a well-designed strategy, including technical training, clearly defined roles and responsibilities, and strong support structure, is important to maximize their potential in the health system.